Implementation of Corporate Social Social Responsibility (CSR) Program Based on Community Empowerment with a Sustainable Environmental Ecology Approach - King Amil Hamzah Al Hakim Shodikin; Abdul Aziz Nasihuddin; Moh. Husein Sastranegara (Green Publisher Indonesia, 2025)
Discussions related to the implementation of Corporate Social Responsibility (CSR) programs are often not accompanied by the impact produced, this often makes the implementation of CSR only limited to charity activities without having an impact on the community in a sustainable manner. The empowerment-based CSR approach model is one of the options in the implementation of programs that are considered to be able to increase the role of the community and make it a subject and not just an object. This research is a qualitative research by taking primary data through observation and interview activities, while secondary data is sourced from supporting documents found in the field. Using an environmental ecology approach, this study looks not only at natural phenomena, but also investigates how human activities can affect the balance of ecosystems and the quality of the environment. The results of this study show that the CSR program has had an impact on 4 main dimensions, namely: the natural dimension, the economic dimension, the social dimension and the wellbeing dimension.